"Egusi" melon seed yield, proximate content and soil nutrient changes with poultry manure fertilization. (14th September 2018) - Makinde, E. A.; Salau, A. W.; Odeyemi, O. M.; Akhimien, O.
Abstract: "Egusi" melon ( Colocynthis citrullus L.) is a seed vegetable whose yield is limited by nutrient supply. Two field experiments were conducted with "Egusi" melon at the Crops Research Farm of the Federal University of Agriculture, Abeokuta, Nigeria, to evaluate response of poultry manure (PM) rate on seed yield, seed proximate content, and changes in soil nutrients. The study was conducted from May to August 2013 and repeated same period in 2014 using PM at: 0, 2, 4, 6, 8, and 10 t ha −1 . With the first planting, seed yields of 458 and 452 kg ha −1 from applications of 6 and 8 t ha −1 PM were similar with the highest of 522 kg ha −1 from application of 10 t ha −1 PM. The second planting, with residual fertilizer effect had a higher seed yield of 242 kg ha −1 from application of 10 t ha −1 PM. Number of seeds per fruit was higher; 183 seeds per fruit in the first planting and 163 seeds per fruit in the second planting, from plants treated with 10 t ha −1 PM. Shelling percent was comparable in both experiments. It was 19.5% with application of 10 t ha −1 PM and 33.4% with the unfertilized plants for the first planting but was 28.0% with application of 10 t ha −1 PM and 31.3% with the unfertilized plants for the second planting. Seed crude protein, crude fiber and ash contents were enhanced with application of 10 t ha −1 PM. Soil pH in the first planting was reduced from initial 6.8 to 6.6 with the unfertilized plants and to 6.7 with applications of 2 and 10 t ha −1 PM, but increased to 7.1 with application of 6 t ha −1 PM. In the second planting, it was reduced to 5.0 with applications of 0, 2 and 4 t ha −1 PM but to 5.3, 5.1, and 5.2 with applications of 6, 8, and 10 t ha −1 PM, respectively. The initial total N of 0.14% was reduced to 0.12% with applications of 6 and 8 t ha −1 PM but to 0.11% with the other treatments in the first planting; but reduced to 0.08% with applications of 2 and 4 t ha −1 PM and to 0.06 and 0.09% with applications of 8 and 10 t ha −1 PM, respectively, in the second planting. Available P in the first planting was reduced from an initial 17.62 mg kg −1 to 4.32 mg kg −1 with the control treatment and to 6.74 and 5.83 mg kg −1 with applications of 2 and 4 t ha −1 PM, respectively, but to 8.32 and 8.24 with applications of 8 and 10 t ha −1 PM, respectively. In the second planting, it was reduced to 1.92 mg kg −1 with the control treatment and to 2.53 and 1.81 mg kg −1 with applications of 2 and 4 t ha −1 PM, respectively but to 1.90 and 1.56 with applications of 8 and 10 t ha −1 PM, respectively. Application of 10 t ha −1 PM supplying 19 kg N, 0.5 kg P and 27 kg K per ha was adequate for enhanced seed yield and proximate contents of "Egusi" melon.